POLITENESS STRATEGIES OF ANTAGONIST CHARACTERS IN THE DIALOGUE OF AVATAR: THE LAST AIRBENDER (2024) SEASON 1 THE SERIES - Deni Salifitrawan; Irfan Hamonangan Tarihoran (GLOBAL: Education Language and Humanity Journal, 2026)
This study investigates how antagonist characters employ politeness strategies in the 2024 live-action adaptation of Avatar: The Last Airbender, with particular attention to the pragmatic functions of positive and negative politeness in asymmetrical power relations. Drawing on Brown and Levinson’s politeness theory, the research adopts a qualitative descriptive approach to analyze selected dialogues of Princess Azula, Prince Zuko, and Fire Lord Ozai in Season 1 of the series. The data were collected through close observation and documentation of character interactions and were analyzed using thematic categorization and contextual interpretation. The findings reveal that politeness strategies in the narrative do not primarily function to maintain social harmony. Instead, positive politeness is frequently instrumentalized as a strategy of manipulation and ideological alignment, particularly by high-power characters, while negative politeness serves divergent roles: as a defensive mechanism for subordinate characters and as a subtle means of authoritarian control for dominant figures. These results challenge conventional interpretations of politeness as inherently cooperative and highlight its morally ambivalent role in hierarchical and conflict-driven discourse. By situating politeness within narrative power dynamics, this study contributes to pragmatics and media discourse analysis by demonstrating how linguistic strategies reflect and reinforce ideological structures in contemporary audiovisual storytelling